The effects of acupuncture on sleep disorders and its underlying mechanism: a literature review of rodent studies - Lee, Seri; Kim, Seung-Nam (Frontiers in Neuroscience, 2023)
Sleep is a set of physiological processes mainly under neurobiological regulation that affect several physiological systems, and sleep disorders are a condition where normal sleep patterns are disturbed. Clinical studies have confirmed the effects of acupuncture on sleep duration and quality. Although many studies have explored the therapeutic effects of acupuncture on sleep disorders, the mechanisms are unclear. We investigated the mechanism of acupuncture efficacy in a rodent model of sleep disorders and evaluated the therapeutic effects of acupuncture treatment. According to our results, sleep disorders are associated with several brain regions and neurotransmitters. Furthermore, this review showed that neurological processes, such as catecholamine and BDNF signaling pathways, can be regulated by acupuncture, which is a crucial aspect of the acupuncture mechanism in sleep disorders.